RELATIONSHIP OF KNOWLEDGE LEVEL OF FE TABLET WITH COMSUMPTION OF FE TABLET COMPLIANCE IN TRIMESTER III PREGNANT WOMEN AT PUSKESMAS JATIBARANG BREBES - Fatimah, Siti; Sholikatun, Umi (Postgraduate Program , Poltekkes Kemenkes Semarang, 2021)
One of the important nutritional elements when pregnant is iron. The increase in blood volume duringpregnancy will increase the need for iron , the amount needed by pregnant women to prevent anemia is500 mg which functions for the needs of the fetus, placenta, and the mother's own hemoglobin. Jens andthe research design used was descriptive analytic, amounting to 163 pregnant women. The samplingtechnique used simple random sampling of 116 respondents. The analysis used was the frequencydistribution and the bivariate rank Spearman analysis. The results of the study with the RankSpearman correlation test using the SPSS 17 program obtained R count = 0.223 with a level of significant( Î± ) = 0.05, then R table = 0.1824 which means R count> R table and obtained p value = 0.016 whichindicates that the p value <from Î± ( p value 0.016 <0.05) . Pregnant women should increase theirknowledge about iron tablets as a supplement to iron by actively following health education and pregnancyexaminations, so they always consume Fe tablets during pregnancy by taking 1 tablet per day to avoid theincidence of pregnancy anemia. Pregnant women should increase their knowledge about iron tabletsas a supplement to iron by actively participating in health education on antenatal care.Keywords: Knowledge, pregnant women, obedient, Fe tablets